Mask blank and manufacturing method thereof, and phase shift mask and manufacturing method thereof

By introducing an etching cutoff film, a phase shift film, a light-shielding film and a hard mask into the mask blank, combined with a specific material and a laminated structure, the problem that the existing phase shift mask is difficult to meet high resolution and excellent etch resistance at the same time, and a phase shift mask with high resolution and excellent etch resistance is achieved.

CN119805847APending Publication Date: 2025-04-11QINGFANG TECHNOLOGY (JINAN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510095453.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing phase shift masks are difficult to meet high resolution and excellent etch resistance at the same time, and there is also the problem of over-etching of substrates.

Method used

A mask blank is provided, including a light-transmissive substrate, an etch cutoff film, a phase shift film, a light-shielding film and a hard mask, and optimizes optical density and phase difference through specific material combinations and laminated structures to improve resolution and etch resistance, and reduces loss of the resist film by setting the hard mask.

Benefits of technology

A phase shift mask with high resolution and excellent etch resistance is achieved, reducing over-etching of the substrate and improving the uniformity of optical performance during pattern transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805847A_ABST
    Figure CN119805847A_ABST
Patent Text Reader

Abstract

The invention provides a mask blank and a manufacturing method thereof, and a phase shift mask and a manufacturing method thereof. The mask blank comprises a light-transmitting substrate, an etching cut-off film, a phase shift film, a shading film and a hard mask which are sequentially stacked, materials of the etching cut-off film comprise metal elements and non-metal elements, and the metal elements are selected from one of Cr, Ta, Hf, Zr, Al, W and Ni; the material of the phase shift film comprises a molybdenum-silicon compound and a non-metallic element; the shading film is made of Cr and non-metallic elements; the material of the hard mask comprises silicon or a molybdenum-silicon compound and a non-metallic element; the non-metallic element is selected from one or more of C, O, N, B and P.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor manufacturing, and in particular to a mask blank and a manufacturing method thereof, a phase-shift mask and a manufacturing method thereof. Background Art

[0002] In the manufacturing process of semiconductor devices, photolithography is usually used to form fine patterns. In the process of pattern miniaturization using photolithography, in addition to miniaturizing the mask pattern of the transfer mask, it is also necessary to reduce the wavelength of the exposure light source as much as possible. In recent years, the exposure light source used in deep ultraviolet (DUV) lithography has been advanced to ArF excimer laser, which has a wavelength of 193nm.

[0003] Masks mainly include binary masks and phase-shift masks. Phase-shift masks are manufactured by forming a mask pattern on a mask blank through a corresponding photolithography process, wherein the mask blank is composed of different functional film layers such as a phase-shift film, a light-shielding film, and a resist film. The semi-transparent area on the phase-shift mask shifts the phase of light, and the phase difference with the light transmitted through the transparent area is about 180°, so that the light at the boundary between the semi-transparent area and the transparent area cancels each other, partially reducing the diffraction expansion effect, changing the spatial light intensity distribution, and thus improving the spatial pattern contrast at the boundary.

[0004] In order to obtain a fine photomask pattern, on the one hand, the resist pattern needs to be more miniaturized, so a thinner resist film is required. If the film thickness of the resist film is not reduced, the excessively high thickness will cause the aspect ratio of the resist portion used as the light shielding layer to become larger, that is, the ratio of the resist film thickness to the pattern width becomes larger, thereby causing the pattern shape to deteriorate easily, and the resolution of the transfer pattern on the light shielding layer using it as an etching mask is reduced. Even in extreme cases, a part of the resist pattern collapses or peels off, resulting in the formation of a pattern blank. On the other hand, when the light shielding film is patterned using the resist film as an etching mask, a common light shielding film (such as a light shielding film containing a chromium compound) is usually patterned by dry etching, and most etching conditions also have an etching effect that cannot be ignored on organic films such as resist films. If a thinner resist film is used as a mask to etch the light-shielding film, the resist film that is too thin is not enough to block the long-term attack of plasma, causing the resist film to be damaged during the etching process, and then causing the shape of the resist pattern to change, making it difficult to accurately transfer the original resist pattern to the light-shielding film.

[0005] Based on the existing pattern forming process, in order to obtain high resolution, the resist film needs to be thinned, and in order to ensure that the resist film has good etching resistance in the pattern forming process, its thickness needs to be increased. On this basis, the existing organic resist film is difficult to meet both high resolution and excellent etching resistance.

[0006] Moreover, for the mask blank composed of the resist film, the shading film, the phase shift film and the transparent substrate, the shading layer is used as a mask. During the dry etching of the phase shift film, the transparent substrate is easily over-etched and the etching is uneven, which leads to uneven phase shift in the subsequent pattern transfer process.

[0007] Therefore, in order to form a higher resolution photomask pattern, realize thinning of the resist film, improve the etching resistance, and reduce the over-etching of the substrate, it is urgent to provide a phase shift mask and a method for manufacturing the same. Summary of the invention

[0008] The main purpose of the present invention is to provide a mask blank and a manufacturing method thereof, a phase-shift mask and a manufacturing method thereof, so as to solve the problem that the existing phase-shift masks in the prior art are difficult to simultaneously meet the requirements of high resolution and excellent etching resistance, and the substrate is prone to over-etching.

[0009] In order to achieve the above-mentioned purpose, the present invention provides a mask blank on one hand, which includes a translucent substrate, an etching stop film, a phase shift film, a shading film and a hard mask which are stacked in sequence, wherein the material of the etching stop film includes metal elements and non-metal elements, and the metal element is selected from one of Cr, Ta, Hf, Zr, Al, W and Ni; the material of the phase shift film includes molybdenum silicon compound and non-metal elements; the material of the shading film includes Cr and non-metal elements; the material of the hard mask includes silicon or molybdenum silicon compound, and non-metal elements; the non-metal elements are selected from one or more of C, O, N, B and P; the light density of the shading film under an exposure light source with a wavelength of ≤250nm is 1.5-2.1; the optical density of the stacked structure obtained by stacking the etching stop film, the phase shift film and the shading film in sequence under an exposure light source with a wavelength of ≤250nm is 2.9-3.3; the transmittance of the etching stop film and the phase shift film under an exposure light source with a wavelength of 193nm is 3-35%, and the phase difference is 175-182°.

[0010] Furthermore, the etching stop film is a single-layer or multi-layer structure with a thickness of 1-10 nm. In each layer of the etching stop film, the atomic percentage of Cr is ≥30 at.%, the atomic percentage of C is ≤15 at.%, and the remainder is other elements.

[0011] Furthermore, the phase shift film is a single-layer or multi-layer structure with a thickness of 60 to 90 nm.

[0012] Furthermore, the phase-shift film is a single-layer structure, wherein the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%.

[0013] Furthermore, the phase-shift film has a two-layer structure, and the atomic percentage of O in the film layer on the side away from the etching stop film is lower than the atomic percentage of O in the film layer on the side close to the etching stop film; wherein, the atomic percentage of Mo in the film layer on the side close to the etching stop film is ≤10at.%, the atomic percentage of Si is ≥30at.%, the atomic percentage of O is ≤25at.%, and the atomic percentage of N is ≥35at.%; the atomic percentage of Mo in the film layer on the side away from the transparent substrate is ≤10at.%, the atomic percentage of Si is ≥30at.%, the atomic percentage of O is ≤20at.%, and the atomic percentage of N is ≥40at.%; the thickness of the film layer on the side close to the etching stop film is 5-45nm, and the thickness of the film layer on the side away from the etching stop film is 30-70nm.

[0014] Furthermore, the light-shielding film is a single-layer or multi-layer structure with a thickness of 30 to 65 nm.

[0015] Furthermore, the light-shielding film is a single-layer structure, wherein the atomic percentage of Cr is ≥30 at.%, the sum of the atomic percentages of O and N is ≤55 at.%, and the atomic percentage of C is ≤15 at.%.

[0016] Furthermore, the shading film has a two-layer structure, and the relative refractive index of the film layer on the side away from the phase shift film is greater than the relative refractive index of the film layer on the side close to the phase shift film; wherein, the atomic percentage of Cr in the film layer close to the phase shift film is ≤43at.%, the sum of the atomic percentages of O and N is ≥37at.%, and the atomic percentage of C is ≤20at.%, wherein, the atomic percentage of Cr in the layer away from the phase shift film is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the film layer close to the phase shift film is 35-55nm, and the thickness of the layer away from the phase shift film is 2-10nm.

[0017] Furthermore, the shading film also includes a diffusion prevention layer, which is arranged on a side close to the phase shift film, wherein the atomic percentage of Cr in the diffusion prevention layer is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the diffusion prevention layer is 2 to 10nm.

[0018] Furthermore, the light-shielding film has a three-layer structure, comprising a first light-shielding layer, a second light-shielding layer and a third light-shielding layer which are stacked in sequence, the first light-shielding layer is arranged on a side close to the phase-shift film, and the third light-shielding layer is far away from the phase-shift film, wherein the atomic percentage of Cr in the first light-shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥35at.%, the atomic percentage of C is ≤20at.%, the atomic percentage of Cr in the second light-shielding layer is ≥45at.%, the atomic percentage of non-metallic elements is ≤55at.%, the atomic percentage of Cr in the third light-shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥35at.%, and the atomic percentage of C is ≤20at.%; the thickness of the first light-shielding layer is 10-35nm, the thickness of the second light-shielding layer is 2-10nm, and the thickness of the third light-shielding layer is 10-30nm.

[0019] Furthermore, the light-shielding film has a four-layer structure, which includes a first light-shielding layer, a second light-shielding layer, a third light-shielding layer and a fourth light-shielding layer which are stacked in sequence, the first light-shielding layer is arranged on a side close to the phase-shift film, and the fourth light-shielding layer is arranged on a side away from the phase-shift film, wherein the atomic percentage of Cr in the first light-shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥40at.%, the atomic percentage of C is ≤15at.%, the atomic percentage of Cr in the second light-shielding layer is ≥35at.%, and the atomic percentage of the third non-metallic element is ≥40at.%. The content is ≤65at.%, the atomic percentage of Cr in the third shading layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥40at.%, the atomic percentage of C is ≤15at.%, the atomic percentage of Cr in the fourth shading layer is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the first shading layer is 15-30nm, the thickness of the second shading layer is 2-10nm, the thickness of the third shading layer is 15-30nm, and the thickness of the fourth shading layer is 2-10nm.

[0020] Furthermore, the hard mask is a single-layer or multi-layer structure with a thickness of 2-15 nm. The atomic percentage of Si in each layer of the hard mask is ≥30 at.%, and the sum of the atomic percentages of O and N is ≤70 at.%.

[0021] Furthermore, the mask blank further comprises a resist film, and the resist film is arranged on a surface of the hard mask away from the light-transmitting substrate; the thickness of the resist film is 60 to 200 nm.

[0022] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a method for manufacturing a mask blank, wherein an etching stop film, a phase shift film, a shading film and a hard mask are deposited on the surface of one side of a light-transmitting substrate in sequence, and the etching stop film, the phase shift film, the shading film and the hard mask have the same definitions as in the previous text.

[0023] Furthermore, magnetron sputtering is used for deposition; during the deposition of the etching cut-off film, the phase shift film, the shading film and the hard mask, the working pressure is independently 0.1-0.4 Pa, the sputtering power is independently 200-3500 W, and the working gas is independently one or more of Ar, He, O2, N2, N2O, NO, NO2, CO2, CO, and CH4.

[0024] Another aspect of the present invention provides a method for manufacturing a phase-shift mask, using the above-mentioned mask blank provided in the present application as a raw material to manufacture a phase-shift mask, the manufacturing method comprising:

[0025] Step S1, coating a first resist on a side of a hard mask in a mask blank away from a light-transmitting substrate to form a resist film, and sequentially performing exposure, baking and development to obtain a first stacked structure including a patterned first resist film;

[0026] Step S2, using the patterned first resist film in the first stacked structure as a mask, etching the hard mask in the first stacked structure, and obtaining a second stacked structure including the patterned hard mask after cleaning and removing the patterned first resist film;

[0027] Step S3, using the patterned hard mask film in the second stacked structure as a mask, etching the light shielding film in the second stacked structure to obtain a third stacked structure including the patterned first light shielding film;

[0028] Step S4, using the patterned first light shielding film in the third stacked structure as a mask, etching the phase shift film in the third stacked structure, during the etching process of step S4, the patterned hard mask film is removed to obtain a fourth stacked structure containing a patterned phase shift film;

[0029] Step S5, coating a second resist on a surface of the fourth stacked structure away from the light-transmitting substrate, and sequentially performing exposure, baking and development to obtain a fifth stacked structure including a patterned second resist film;

[0030] In step S6, the first light-shielding film in the fifth stacked structure is etched using the patterned second resist film in the fifth stacked structure as a mask. During the etching process of step S6, the etching stop film is etched away. After cleaning and removing the patterned second resist film, a phase-shift mask containing the patterned second light-shielding film is obtained.

[0031] Furthermore, the hard mask is a single-layer structure, or the hard mask is a two-layer structure, and the etching rate of the film layer close to the light-shielding film is lower than the etching rate of the film layer away from the light-shielding film; or the hard mask is a three-layer structure, and the etching rate of the middle layer is lower than the etching rates of the other two layers.

[0032] Another aspect of the present invention provides a phase-shift mask, which is manufactured using the method for manufacturing the phase-shift mask provided in the present application.

[0033] By applying the technical solution of the present invention, a hard mask is provided on the surface of the mask blank on the side of the light shielding film away from the light-transmitting substrate. Since the hard mask is thin, the loss of the resist film provided on one side of the hard mask is reduced when etching the hard mask in the process of manufacturing the phase-shift mask, and the thickness of the resist film can be reduced to achieve the effect of high resolution and small line width.

[0034] In addition, since the etching time required for hard mask patterning is shorter than that required for light shielding film patterning, the provision of the hard mask can alleviate the load effect occurring during pattern formation and improve CD (critical dimension) linearity.

[0035] Compared with the mask blank without an etching stop film, the mask blank provided in the present application has an etching stop film on the surface of the translucent substrate. In the process of etching the phase shift film using the shading film as a mask, excessive etching of the translucent substrate can be avoided, thereby solving the problem of uneven phase shift in the subsequent pattern transfer process. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0037] Figure 1 A schematic cross-sectional structure diagram of a mask blank provided in the present application is shown;

[0038] Figure 2 A schematic cross-sectional structure diagram of a mask blank in one embodiment of the present application is shown;

[0039] Figure 3 shows a schematic cross-sectional structure diagram of a first stacked structure;

[0040] Figure 4 shows a schematic cross-sectional structure diagram of a second stacked structure;

[0041] Figure 5 shows a schematic cross-sectional structure diagram of a third laminated structure;

[0042] Figure 6 shows a schematic cross-sectional structure diagram of a fourth stacked structure;

[0043] Figure 7 shows a schematic cross-sectional structure diagram of a fifth stacked structure;

[0044] Figure 8 A schematic cross-sectional structure diagram of a phase-shift mask is shown;

[0045] Fig. 9 A schematic cross-sectional structure diagram of the mask blank of Comparative Example 2 is shown.

[0046] The above drawings include the following reference numerals:

[0047] 10. Transparent substrate; 20. Etching stop film; 30. Phase shift film; 31. Patterned phase shift film; 40. Shading film; 41. Patterned first shading film; 42. Patterned second shading film; 50. Hard mask; 51. Patterned hard mask; 60. Resist film; 61. Patterned first resist film; 62. Patterned second resist film. DETAILED DESCRIPTION

[0048] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0049] As described in the background art, the existing phase-shift mask is difficult to meet the requirements of high resolution and excellent etching resistance at the same time, and there is also the problem that the substrate is prone to over-etching. In order to solve the above technical problems, the first aspect of the present application provides a mask blank, Figure 1 The cross-sectional structure schematic diagram of the mask blank is shown. The mask blank includes a light-transmitting substrate 10, an etching stop film 20, a phase shift film 30, a light shielding film 40 and a hard mask film 50 which are stacked in sequence.

[0050] Among them, the material of the etching stop film 20 includes metal elements and non-metal elements, and the metal element is selected from one of Cr, Ta, Hf, Zr, Al, W and Ni; the material of the phase shift film 30 includes molybdenum silicon compound and non-metal elements; the material of the shading film 40 includes Cr and non-metal elements; the material of the hard mask 50 includes silicon or molybdenum silicon compound, and non-metal elements; the non-metal elements are selected from one or more of C, O, N, B and P; the optical density of the shading film 40 under an exposure light source with a wavelength of ≤250nm is 1.5-2.1; the optical density of the stacked structure obtained by stacking the etching stop film 20, the phase shift film 30 and the shading film 40 in sequence under an exposure light source with a wavelength of ≤250nm is 2.9-3.3; the transmittance of the etching stop film 20 and the phase shift film 30 under an exposure light source with a wavelength of 193nm is 3-35%, and the phase difference is 175-182°.

[0051] In the process of manufacturing the phase-shift mask, the hard mask 50 can reduce the loss of the resist film 60 on its surface, and can reduce the thickness of the resist film 60 to achieve high resolution and small line width. Compared with other types, the hard mask 50 made of the above material is conducive to reducing the thickness of the resist film 60 and reducing the loss of the resist film 60 during the patterning process.

[0052] The mask blank provided in the present application is provided with an etching stop film 20. Compared with the mask blank without the etching stop film 20, in the process of etching the phase shift film 30, it is possible to avoid excessive etching of the light-transmitting substrate 10, and improve the uniformity of optical performance in the later pattern transfer process. Compared with other types, the etching stop film 20 made of the above-mentioned specific material is used, and the material of the etching stop film 20 is different from that of the phase shift film 30 and the light-transmitting substrate 10, which is conducive to preventing excessive etching of the light-transmitting substrate 10 and improving the uniformity of optical performance in the later pattern transfer process.

[0053] Compared with other types, the phase shift film 30 made of the above-mentioned specific material can optimize the light field distribution, can perform destructive interference, reduce the brightness of the dark area in the light field, and increase the brightness of the bright area in the light field, thereby improving the resolution of the prepared phase shift mask and reducing the line width. Moreover, compared with other ranges, limiting the optical density of the etching stop film 20, the phase shift film 30 and the light shielding film 40 to the above-mentioned specific range can play the light shielding role of the mask blank, improve the blocking effect on the exposure light source, improve the resolution of the phase shift mask, and further improve the resolution of the pattern formed by exposure on the wafer surface.

[0054] In a preferred embodiment, the etching stop film 20 is a single-layer or multi-layer structure with a thickness of 1 to 10 nm. The atomic percentage of Cr in each layer of the etching stop film 20 is ≥30 at.%, the atomic percentage of C is ≤15 at.%, and the remainder is other elements.

[0055] In a preferred embodiment, the phase shift film 30 is a single-layer or multi-layer structure with a thickness of 60-90 nm.

[0056] In a preferred embodiment, the phase shift film 30 is a single-layer structure, wherein the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%.

[0057] In a preferred embodiment, the phase shift film 30 is a two-layer structure, and the atomic percentage of O in the film layer on the side away from the etching stop film 20 is lower than the atomic percentage of O in the film layer on the side close to the etching stop film 20; wherein, the atomic percentage of Mo in the film layer on the side close to the etching stop film 20 is ≤10at.%, the atomic percentage of Si is ≥30at.%, the atomic percentage of O is ≤25at.%, and the atomic percentage of N is ≥35at.%; the atomic percentage of Mo in the film layer on the side away from the etching stop film 20 is ≤10at.%, the atomic percentage of Si is ≥30at.%, the atomic percentage of O is ≤20at.%, and the atomic percentage of N is ≥40at.%; the thickness of the film layer on the side close to the etching stop film 20 is 5-45nm, and the thickness of the film layer on the side away from the etching stop film 20 is 30-70nm.

[0058] In a preferred embodiment, the light shielding film 40 is a single-layer structure or a multi-layer structure, and has a thickness of 30-65 nm.

[0059] In a preferred embodiment, the light shielding film 40 is a single-layer structure, the atomic percentage of Cr in the light shielding film 40 is ≥30 at.%, the sum of the atomic percentages of O and N is ≤55 at.%, and the atomic percentage of C is ≤15 at.%.

[0060] In a preferred embodiment, the shading film 40 is a two-layer structure, and the relative refractive index of the film layer on the side away from the phase shift film 30 is greater than the relative refractive index of the film layer on the side close to the phase shift film 30; wherein, the atomic percentage of Cr in the film layer close to the phase shift film 30 is ≤43at.%, the sum of the atomic percentages of O and N is ≥37at.%, and the atomic percentage of C is ≤20at.%; the atomic percentage of Cr in the film layer away from the phase shift film 30 is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the film layer close to the phase shift film 30 is 35-55nm, and the thickness of the film layer away from the phase shift film 30 is 2-10nm.

[0061] In a more preferred embodiment, the above-mentioned two-layer shading film 40 also includes a diffusion prevention layer, which is arranged on a side close to the phase shift film 30, wherein the atomic percentage of Cr in the diffusion prevention layer is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the diffusion prevention layer is 2 to 10nm.

[0062] In a preferred embodiment, the light-shielding film 40 is a three-layer structure, which includes a first light-shielding layer, a second light-shielding layer and a third light-shielding layer which are stacked in sequence. The first light-shielding layer is arranged on a side close to the phase-shift film 30, and the third light-shielding layer is arranged on a side away from the phase-shift film 30, wherein the atomic percentage of Cr in the first light-shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥35at.%, and the atomic percentage of C is ≤20at.%; the atomic percentage of Cr in the second light-shielding layer is ≥45at.%, and the atomic percentage of non-metallic elements is ≤55at.%; the atomic percentage of Cr in the third light-shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥35at.%, and the atomic percentage of C is ≤20at.%; the thickness of the first light-shielding layer is 10-35nm, the thickness of the second light-shielding layer is 2-10nm, and the thickness of the third light-shielding layer is 10-30nm.

[0063] In a preferred embodiment, the light shielding film 40 is a four-layer structure, which includes a first light shielding layer, a second light shielding layer, a third light shielding layer and a fourth light shielding layer which are stacked in sequence. The first light shielding layer is arranged on a side close to the phase shift film 30, and the fourth light shielding layer is arranged on a side away from the phase shift film 30. The atomic percentage of Cr in the first light shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥40at.%, and the atomic percentage of C is ≤15at.%; the atomic percentage of Cr in the second light shielding layer is ≥35at.%, and the non-metallic element The atomic percentage of the element is ≤65at.%; the atomic percentage of Cr in the third shading layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥40at.%, and the atomic percentage of C is ≤15at.%; the atomic percentage of Cr in the fourth shading layer is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the first shading layer is 15-30nm, the thickness of the second shading layer is 2-10nm, the thickness of the third shading layer is 15-30nm, and the thickness of the fourth shading layer is 2-10nm.

[0064] In a preferred embodiment, the hard mask 50 is a single-layer or multi-layer structure with a thickness of 2 to 15 nm. Compared with other ranges, the thickness of the hard mask 50 is limited to the above range. Since the thickness of the hard mask 50 is thin, it is beneficial to reduce the loss of the resist film 60 on its surface when etching it in the process of manufacturing the phase-shift mask, which is beneficial to thinning the thickness of the resist film 60 and achieving higher resolution and smaller line width.

[0065] In a preferred embodiment, the atomic percentage of Si in each layer of the hard mask 50 is ≥30 at.%, and the sum of the atomic percentages of O and N is ≤70 at.%.

[0066] In a preferred embodiment, Figure 2 As shown, the mask blank further includes a resist film 60, which is disposed on a surface of the hard mask 50 that is away from the light-transmitting substrate 10. The resist film 60 is disposed to facilitate exposure processing and patterning and subsequent manufacture of a phase-shift mask.

[0067] In order to improve the resolution of the pattern formed by etching, in a preferred embodiment, the thickness of the resist film 60 is 60-200 nm.

[0068] In order to improve the resolution of the pattern formed by etching, in a preferred embodiment, the resist film 60 is a chemically amplified resist.

[0069] It should be noted that the thickness of each film layer mentioned above in the present application can be measured by XRR (X-ray reflectivity); the chemical composition of the film layer can be measured by XPS (X-ray photoelectron spectroscopy).

[0070] The second aspect of the present application also provides a method for manufacturing a mask blank, which includes sequentially depositing an etching stop film 20, a phase shift film 30, a shading film 40 and a hard mask 50 on a surface of one side of a light-transmitting substrate 10, wherein the etching stop film 20, the phase shift film 30, the shading film 40 and the hard mask 50 have the same definitions as those in the previous text of the present application.

[0071] By using a deposition method to sequentially prepare an etching stop film 20, a phase shift film 30, a light shielding film 40 and a hard mask film 50 on one side surface of a light-transmitting substrate 10, a mask blank of the above-mentioned laminated structure of the present application can be obtained.

[0072] In a preferred embodiment, magnetron sputtering is used for deposition. Compared with other methods, magnetron sputtering is advantageous for controlling the deposition effect, thereby improving the performance of each film layer, and further improving the resolution of the phase-shift mask.

[0073] In a preferred embodiment, during the deposition of the etching stop film 20, the phase shift film 30, the shading film 40 and the hard mask 50, the working pressure is independently 0.1-0.4 Pa, the sputtering power is independently 200-3500 W, and the working gas is independently one or more of Ar, He, O2, N2, N2O, NO, NO2, CO2, CO, and CH4.

[0074] The third aspect of the present application also provides a method for manufacturing a phase-shift mask, using the above-mentioned mask blank provided in the present application as a raw material to manufacture a phase-shift mask, the manufacturing method comprising:

[0075] Step S1, coating a first resist on the side of the hard mask 50 in the mask blank away from the light-transmitting substrate 10 to form a resist film 60, and sequentially performing exposure, baking and development to obtain a first stacked structure (such as Figure 3 shown);

[0076] Step S2, using the patterned first resist film 61 in the first stacked structure as a mask, etching the hard mask film 50 in the first stacked structure, and after cleaning and removing the patterned first resist film 61, obtaining a second stacked structure (such as Figure 4 shown);

[0077] Step S3, using the patterned hard mask 51 in the second stacked structure as a mask, etching the light shielding film 40 in the second stacked structure to obtain a third stacked structure (such as Figure 5 shown);

[0078] Step S4, using the patterned first light shielding film 41 in the third stacked structure as a mask, etching the phase shift film 30 in the third stacked structure. During the etching process in step S4, the patterned hard mask 51 is removed to obtain a fourth stacked structure (such as Figure 6 shown);

[0079] Step S5, coating a second resist on the surface of the side away from the light-transmitting substrate 10 in the fourth stacked structure, and sequentially performing exposure, baking and development to obtain a fifth stacked structure (such as Figure 7 shown);

[0080] Step S6, using the patterned second resist film 62 in the fifth stacked structure as a mask, etching the first light shielding film 41 in the fifth stacked structure, during the etching process in step S6, the etching stop film 20 is etched away, and after cleaning and removing the patterned second resist film 62, a phase shift mask (such as Figure 8 shown).

[0081] In a preferred embodiment, the etching is preferably dry etching.

[0082] In a preferred embodiment, in step S2, a mixed gas of SF6 and He with a gas flow ratio of 1:15 is used to dry-etch the hard mask 50 in the first stacked structure; in step S3, a mixed gas of Cl2 and O2 with a gas flow ratio of 10:1 is used to dry-etch the shading film 40 in the second stacked structure; in step S4, a mixed gas of SF6 and He with a gas flow ratio of 1:15 is used to dry-etch the phase shift film 30 in the third stacked structure; in step S6, a mixed gas of Cl2 and O2 with a gas flow ratio of 7:2 is used to dry-etch the first shading film 41 in the fifth stacked structure.

[0083] By using the mask blank of the specific stacked structure and material provided in the present application as a raw material and adopting the above manufacturing method for manufacturing, a phase shift mask with high resolution and excellent etching resistance can be obtained.

[0084] In a preferred embodiment, the hard mask 50 is a single-layer structure, or the hard mask 50 is a two-layer structure, and the etching rate of the film layer close to the side of the shading film 40 is lower than the etching rate of the film layer away from the side of the shading film 40; or the hard mask 50 is a three-layer structure, and the etching rate of the middle layer is lower than the etching rates of the other two adjacent layers.

[0085] The fourth aspect of the present application also provides a phase-shift mask, which is manufactured using the manufacturing method of the phase-shift mask provided in the present application. By using the mask blank of the specific laminated structure and material provided in the present application as a raw material and manufacturing it using the manufacturing method, a phase-shift mask with high resolution and excellent etching resistance can be obtained.

[0086] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0087] Example 1

[0088] A method for manufacturing a mask blank, comprising:

[0089] (1) preparing a transparent substrate 10 of quartz glass with a size of 152 mm×152 mm×6.35 mm as a mask blank and cleaning the substrate 10, wherein the surface root mean square roughness Rq of the transparent substrate 10 is less than 0.5 nm;

[0090] (2) Preparation of etching stop film 20:

[0091] Direct current (DC) reactive magnetron sputtering was performed on one side surface of the light-transmitting substrate 10, the target material was a chromium (Cr) target, a mixed gas of Ar, N2, and O2 was used as the working gas (wherein the gas flow ratio of Ar, O2, and N2 was 60:1:20), the working gas pressure was set to 0.13 Pa, and the power of the DC power supply was 600 W, to obtain a CrON single-layer film with a thickness of 3 nm;

[0092] The chemical composition of the CrON single-layer film was measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the CrON single-layer film was measured as follows: the atomic percentage of Cr was 55 at.%, the atomic percentage of O was 8 at.%, and the atomic percentage of N was 37 at.%;

[0093] (3) Preparation of phase shift film 30:

[0094] Direct current (DC) magnetron sputtering is performed on the surface of the etching stop film 20 away from the transparent substrate 10, the target material is a molybdenum silicon (MoSi) alloy target, a mixed gas of Ar and N2 is used as the working gas (wherein, N2 gas flow / (Ar gas flow+N2 gas flow)=85%), the working gas pressure is set to 0.13 Pa, and the power of the DC power supply is 600 W, to obtain a MoSi single-layer film (i.e., the phase shift film 30) with a thickness of 66 nm;

[0095] The chemical composition of the MoSi single-layer film was measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the MoSi single-layer film was measured to be: Mo=4.4at.%, Si=40.1at.%, N=55.5at.%; the content of each of the above elements is within the atomic percentage content limit range of the phase shift film 30 of the present application (that is, the Mo atomic percentage content is ≤10at.%, the Si atomic percentage content is ≥30at.%, and the N atomic percentage content is ≥40at.%);

[0096] The optical performance of the phase shift film 30 was simulated based on the above-mentioned related measured parameters. The results showed that the total transmittance of the phase shift film 30 and the etched cut-off film 20 was 6.0% under 193nm wavelength light, and the total phase shift was 179.8°;

[0097] (4) Preparation of light shielding film 40:

[0098] Three layers are sequentially deposited on the surface of the phase shift film 30 away from the light-transmitting substrate 10 to obtain a light-shielding film 40 having a three-layer structure; wherein the film layers close to the phase shift film 30 are sequentially the first light-shielding layer and the second light-shielding layer, and the film layer away from the phase shift film 30 is the third light-shielding layer;

[0099] The first light-shielding layer is deposited by direct current reactive magnetron sputtering, the target material is a chromium (Cr) target, a mixed gas of Ar, N2 and O2 is used as the working gas (wherein the gas flow ratio of Ar, O2 and N2 is 24:5:30), the working gas pressure is set to 0.13Pa, the power of the DC power supply is 450W, and a CrON film layer with a thickness of 18nm is obtained. The chemical composition of the first light-shielding layer is measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the first light-shielding layer is measured to be: Cr = 41at.%, O = 49at.%, N = 10at.%;

[0100] The second light-shielding layer is also deposited by direct current reactive magnetron sputtering, the target material is a chromium (Cr) target, a mixed gas of Ar, N2 and O2 is used as the working gas (wherein the gas flow ratio of Ar, O2 and N2 is 60:1:20), the working gas pressure is set to 0.13 Pa, the power of the DC power supply is 600W, and a CrON film layer with a thickness of 5nm is obtained. The chemical composition of the second light-shielding layer is measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the second light-shielding layer is measured to be: Cr = 55at.%, O = 8at.%, N = 37at.%;

[0101] The third light-shielding layer is also deposited by direct current reactive magnetron sputtering, the target material is a chromium (Cr) target, a mixed gas of Ar, N2 and O2 is used as the working gas (wherein the gas flow ratio of Ar, O2 and N2 is 24:5:30), the working gas pressure is set to 0.13 Pa, the sputtering power is 450W, and a CrON film layer with a thickness of 21nm is deposited. The chemical composition of the third light-shielding layer is measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the third light-shielding layer is measured to be: Cr = 41at.%, O = 49at.%, N = 10at.%;

[0102] The optical density OD of the stacked structure of the etched stop film 20 / phase shift film 30 / light shielding film 40 prepared in step (4) at a wavelength of 193 nm was measured using an ultraviolet spectrophotometer, and the result was 3.2, which meets the requirement of the optical density in the range of 2.9 to 3.3 of the present application, wherein the optical density of the light shielding film 40 is 1.98, which meets the requirement of the optical density of the light shielding film 40 in the range of 1.5 to 2.1 of the present application;

[0103] (5) Preparation of hard mask 50:

[0104] Direct current (DC) magnetron sputtering is performed on the surface of the light shielding film 40 away from the light-transmitting substrate 10, the target material is a silicon (Si) target material, a mixed gas of Ar and O2 is used as the working gas (wherein the gas flow ratio of Ar and O2 is 1:5), the working gas pressure is set to 0.13 Pa, the power of the DC power supply is 500 W, and a SiO2 single-layer film (i.e., the hard mask 50) with a thickness of 5 nm is obtained;

[0105] The chemical composition of the SiO2 single-layer film was measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the SiO2 single-layer film was measured to be: Si = 65.1 at.%, O = 34.9 at.%.

[0106] The cross-sectional structure diagram of the mask blank prepared in Example 1 is as follows Figure 1 shown.

[0107] A method for manufacturing a phase shift mask, using the mask blank prepared in Example 1, comprising:

[0108] (1) The surface of the hard mask 50 in the mask blank is treated with HMDS (hexamethyldisilazane) to improve the adhesion between the resist film 60 and the hard mask 50, and a 100 nm thick chemically amplified resist film 60 sensitive to electron beams is spin-coated on the surface of the hard mask 50; then, an electron beam exposure machine is used to expose the hard mask 50, and the wavelength of the exposure light source is 193 nm. After baking and developing, a first stacked structure (such as Figure 3 shown);

[0109] (2) Using the patterned first resist film 61 in the first stacked structure as a mask, a mixed gas of SF6 and He with a gas flow ratio of 1:15 is used to dry-etch the hard mask film 50 in the first stacked structure, and the patterned first resist film 61 is removed by wet cleaning to obtain a second stacked structure containing the patterned hard mask 51 (such as Figure 4 As shown), the cleaning agent is a combination of SPM (containing H2SO4, H2O2 and H2O), SC1 (containing NH4OH, H2O2 and H2O) and deionized water;

[0110] (3) Using the patterned hard mask 51 as a mask, a mixed gas of Cl2 and O2 with a gas flow ratio of 10:1 is used to dry-etch the light shielding film 40 in the second stacked structure to obtain a third stacked structure including the patterned first light shielding film 41 (e.g. Figure 5 shown);

[0111] (4) Using the patterned first light shielding film 41 in the third stacked structure as a mask, the phase shift film 30 in the third stacked structure is dry-etched using a mixed gas of SF6 and He with a gas flow ratio of 1:15. During the etching process of step (4), the patterned hard mask film 51 is removed to obtain a fourth stacked structure (such as Figure 6 shown);

[0112] (5) A layer of a 150 nm thick chemically amplified resist film sensitive to electron beams is spin-coated on the surface of the fourth stacked structure on the side away from the light-transmitting substrate 10; then, an electron beam exposure device is used to expose the resist film, and the wavelength of the exposure light source is 193 nm. After baking and development, a fifth stacked structure (such as Figure 7 shown);

[0113] (6) Using the patterned second resist film 62 in the fifth stacked structure as a mask, a mixed gas of Cl2 and O2 with a gas flow ratio of 7:2 is used to dry-etch the first shading film 41 in the fifth stacked structure. During the etching process of step (6), the etching stop film 20 is completely consumed. After the patterned second resist film 62 is removed by wet cleaning, a phase-shift mask containing the patterned second shading film 42 is obtained. Figure 8 A schematic cross-sectional structure diagram of the phase-shift mask is shown.

[0114] Example 2

[0115] The difference from Example 1 is that the phase shift film 30 in the mask blank has a two-layer structure. Specifically, in the process of manufacturing the mask blank, the preparation process of the phase shift film 30 in step (3) includes:

[0116] Direct current (DC) magnetron sputtering is performed on the surface of the etching stop film 20 away from the transparent substrate 10 to obtain a two-layer phase shift film 30. When preparing the first layer, the target material is a molybdenum silicon (MoSi) alloy target, and a mixed gas of Ar and N2 is used as the working gas (wherein, N2 gas flow / (Ar gas flow+N2 gas flow)=83.3%), the working gas pressure is set to 0.15Pa, and the power of the DC power supply is 500W to obtain a MoSiON single-layer film; the thickness of the first MoSiON single-layer film is 34nm, and the content of each element is: Mo=6.2at.%, Si=35.9a t.%, O=11.2at.%, ​​N=46.7at.%; when preparing the second layer, the target material is a molybdenum-silicon (MoSi) alloy target, and a mixed gas of Ar and N2 is used as the working gas (wherein, N2 gas flow rate / (Ar gas flow rate+N2 ​​gas flow rate)=80.0%), the working gas pressure is set to 0.14Pa, and the sputtering power is 500W to obtain a MoSiON single-layer film; the thickness of the second MoSiON single-layer film is 38nm, and the content of each element is: Mo=6.5at.%, ​​Si=37.3at.%, ​​O=9.5at.%, ​​N=46.7at.%.

[0117] The preparation steps of the remaining mask blanks are the same as those in Example 1. The optical density OD of the stacked structure of the etching cut-off film 20 / phase shift film 30 / light shielding film 40 prepared in step (4) at a wavelength of 193 nm was measured using an ultraviolet spectrophotometer, and the result was 3.2. The optical properties of the phase shift film 30 were simulated based on the above-mentioned related measured parameters, and the results showed that the total transmittance of the phase shift film 30 and the etching cut-off film 20 at a wavelength of 193 nm was 6.2%, and the total phase shift was 178.6°.

[0118] The steps for preparing the phase-shift mask are the same as those in Example 1.

[0119] Example 3

[0120] The difference from the first embodiment is that the light shielding film 40 in the mask blank has a single-layer structure and its thickness is 45 nm.

[0121] DC reactive magnetron sputtering was used for deposition, with a chromium (Cr) target as the target material and a mixed gas of Ar, CO2 and N2 as the sputtering gas (wherein the gas flow ratio of Ar, CO2 and N2 was 25:5:4), the working gas pressure was set to 0.3 Pa, and the power of the DC power supply was 700 W to obtain a CrONC film, in which the content of each element was: Cr = 40 at.%, O = 29 at.%, N = 17 at.%, and C = 14 at.%.

[0122] The preparation steps of the remaining mask blanks are the same as those in Example 1. The optical density OD of the stacked structure of the etching stop film 20 / phase shift film 30 / light shielding film 40 prepared in step (4) at a wavelength of 193 nm was measured using an ultraviolet spectrophotometer, and the result was 3.1, wherein the optical density of the light shielding film 40 was 1.91, which met the requirement of the present application that the optical density of the light shielding film 40 was within the range of 1.5 to 2.1.

[0123] The steps for preparing the phase-shift mask are the same as those in Example 1.

[0124] Comparative Example 1

[0125] The difference from Example 1 is that in the preparation process of the mask blank of Comparative Example 1, the preparation process of the phase shift film 30 in step (3) is different from that in Example 1, specifically, it includes:

[0126] Direct current (DC) magnetron sputtering is performed on the surface of the etching stop film 20 away from the transparent substrate 10, the target material is a molybdenum silicon (MoSi) alloy target, a mixed gas of Ar and N2 is used as the working gas (wherein, N2 gas flow / (Ar gas flow+N2 gas flow)=33%), the working gas pressure is set to 0.13 Pa, and the power of the DC power supply is 500 W, to obtain a MoSi single-layer film (i.e., the phase shift film 30);

[0127] The chemical composition of the MoSi single layer film was measured by XPS (X-ray photoelectron spectroscopy), and the content of each element in the MoSi single layer was measured to be: Mo = 16.4 at.%, Si = 63.7 at.%, N = 19.9 at.%; the above element contents are not within the atomic percentage content limit range of the phase shift film 30 of the present application (Mo atomic percentage ≤ 10 at.%, Si atomic percentage ≥ 30 at.%, N atomic percentage ≥ 40 at.%);

[0128] The optical performance of the phase shift film 30 was simulated based on the above-mentioned related measured parameters. The results show that at a wavelength of 193nm, within the allowable film thickness range (60-90nm), the above-mentioned phase shift film 30 and etching cut-off film 20 prepared on a light-transmitting substrate cannot simultaneously meet the requirements of the total transmittance and total phase difference of the phase shift film 30 and the etching cut-off film 20 (the transmittance of the etching cut-off film 20 and the phase shift film 30 under the exposure light source with a wavelength of 193nm is 3-35%, and the phase difference is 175-182°).

[0129] Comparative Example 2

[0130] The difference from Example 1 is: Fig. 9As shown, the mask blank of comparative example 2 does not have an etching stop film 20, and the thickness of the MoSi single-layer film (i.e., the phase shift film 30) obtained in step (3) is 69 nm, wherein the contents of each element are: Mo = 4.9 at.%, Si = 39.9 at.%, and N = 55.2 at.%.

[0131] The element contents of the phase shift film 30 in the mask blank prepared in Comparative Example 2 are all within the atomic percentage content limit range of the phase shift film 30 of the present application (Mo atomic percentage ≤ 10 at.%, Si atomic percentage ≥ 30 at.%, N atomic percentage ≥ 40 at.%);

[0132] The optical performance of the phase shift film 30 of the mask blank in comparative example 2 was simulated based on the above-mentioned relevant measured parameters. The results show that the total transmittance of the etching cut-off film 20 and the phase shift film 30 under the light with a wavelength of 193nm is 6.2%, and the total phase difference is 177.7°; the total transmittance and total phase difference of the etching cut-off film 20 and the phase shift film 30 are both within the range of 3-35% and 175-182° of the light transmittance of the etching cut-off film 20 and the phase shift film 30 under the exposure light source with a wavelength of 193nm in the present application. The optical density OD of the stacked structure of the phase shift film 30 and the light shielding film 40 of the mask blank in comparative example 2 was measured using an ultraviolet spectrophotometer, and the result was 2.97, which meets the requirement of the present application that the optical density is within the range of 2.9-3.3.

[0133] The process of preparing a binary mask using the mask blank prepared in Comparative Example 2 comprises the following steps:

[0134] (1) The surface of the hard mask 50 in the mask blank is treated with HMDS (hexamethyldisilazane) to improve the adhesion between the resist film 60 and the hard mask 50, and a layer of a chemically amplified resist film 60 with a thickness of 100 nm and sensitive to electron beams is spin-coated on the surface of the hard mask 50; then, an electron beam exposure machine is used to expose the hard mask 50, and the wavelength of the exposure light source is 193 nm. After baking and developing, a first stacked structure (such as Figure 3 shown);

[0135] (2) Using the patterned first resist film 61 in the first stacked structure as a mask, a mixed gas of SF6 and He with a gas flow ratio of 1:15 is used to dry-etch the hard mask film 50 in the first stacked structure, and the patterned first resist film 61 is removed by wet cleaning to obtain a second stacked structure containing the patterned hard mask 51 (such as Figure 4 shown);

[0136] (3) Using the patterned hard mask 51 as a mask, a mixed gas of Cl2 and O2 with a gas flow ratio of 10:1 is used to dry-etch the light shielding film 40 in the second stacked structure to obtain a third stacked structure including the patterned first light shielding film 41 (e.g. Figure 5 shown);

[0137] (4) Using the patterned first light shielding film 41 in the third stacked structure as a mask, the phase shift film 30 in the third stacked structure is dry-etched using a mixed gas of SF6 and He with a gas flow ratio of 1:15. During the etching process of step (4), the patterned hard mask film 51 is removed to obtain a fourth stacked structure (such as Figure 6 shown);

[0138] (5) A 150 nm thick chemically amplified resist film sensitive to electron beams is spin-coated on the surface of the fourth stacked structure on the side away from the light-transmitting substrate 10; then, an electron beam exposure device is used to expose the fourth stacked structure, and the wavelength of the exposure light source is 193 nm. After baking and development, a fifth stacked structure (such as Figure 7 shown);

[0139] (6) Using the patterned second resist film 62 in the fifth stacked structure as a mask, a mixed gas of Cl2 and O2 with a gas flow ratio of 7:2 is used to dry-etch the first shading film 41 in the fifth stacked structure. After wet cleaning is used to remove the patterned second resist film 62, a phase-shift mask containing the patterned second shading film 42 is obtained.

[0140] It is observed that the light-transmitting substrate 10 of the phase-shift mask of Comparative Example 2 is over-etched, and the over-etching is non-uniform, which leads to non-uniform phase shift in the subsequent pattern transfer process.

[0141] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0142] The mask blank provided in the present application is provided with an etching stop film 20. Compared with the mask blank without the etching stop film 20, in the process of etching the phase shift film 30, it is possible to avoid excessive etching of the light-transmitting substrate 10, and improve the uniformity of optical performance in the later pattern transfer process. Compared with other types, the etching stop film 20 made of the above-mentioned specific material is used, and the material of the etching stop film 20 is different from that of the phase shift film 30 and the light-transmitting substrate 10, which is conducive to preventing excessive etching of the light-transmitting substrate 10 and improving the uniformity of optical performance in the later pattern transfer process.

[0143] Compared with other types, the phase shift film 30 made of the above-mentioned specific material can optimize the light field distribution, can perform destructive interference, reduce the brightness of the dark area in the light field, and increase the brightness of the bright area in the light field, thereby improving the resolution of the prepared phase shift mask and reducing the line width. Moreover, compared with other ranges, limiting the optical density of the etching stop film 20, the phase shift film 30 and the light shielding film 40 to the above-mentioned specific range can play the light shielding role of the mask blank, improve the blocking effect on the exposure light source, improve the resolution of the phase shift mask, and further improve the resolution of the pattern formed by exposure on the wafer surface.

[0144] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0145] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A mask blank, characterized in that: The mask blank comprises a light-transmitting substrate (10), an etching stop film (20), a phase shift film (30), a light shielding film (40) and a hard mask film (50) which are stacked in sequence, wherein: The material of the etching stop film (20) includes metal elements and non-metal elements, and the metal element is selected from one of Cr, Ta, Hf, Zr, Al, W and Ni; The material of the phase shift film (30) includes molybdenum silicon compound and non-metallic elements; The material of the light shielding film (40) includes Cr and non-metallic elements; The material of the hard mask (50) includes silicon or molybdenum silicon compound, and non-metallic elements; The non-metallic element is selected from one or more of C, O, N, B and P; The light-shielding film (40) has an optical density of 1.5 to 2.1 under an exposure light source with a wavelength of ≤250 nm; The stacked structure obtained by sequentially stacking the etching stop film (20), the phase shift film (30) and the light shielding film (40) has an optical density of 2.9 to 3.3 under an exposure light source with a wavelength of ≤250nm; The light transmittance of the etching stop film (20) and the phase shift film (30) under an exposure light source with a wavelength of 193 nm is 3 to 35%, and the phase difference is 175 to 182°.

2. The mask blank according to claim 1, characterized in that The etching stop film (20) is a single-layer or multi-layer structure with a thickness of 1 to 10 nm. In each layer of the etching stop film (20), the atomic percentage content of Cr is ≥30 at.%, the atomic percentage content of C is ≤15 at.%, and the remainder is other elements.

3. The mask blank according to claim 1, characterized in that The phase shift film (30) is a single-layer or multi-layer structure with a thickness of 60-90 nm.

4. The mask blank according to claim 3, characterized in that The phase shift film (30) is a single-layer structure, wherein the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%.

5. The mask blank according to claim 3, characterized in that The phase shift film (30) is a two-layer structure, and the atomic percentage of O in the film layer on the side away from the etching stop film (20) is lower than the atomic percentage of O in the film layer on the side close to the etching stop film (20); wherein the atomic percentage of Mo in the film layer on the side close to the etching stop film (20) is ≤10at.%, the atomic percentage of Si is ≥30at.%, the atomic percentage of O is ≤25at.%, and the atomic percentage of N is ≥35at.%; the atomic percentage of Mo in the film layer on the side away from the light-transmitting substrate (10) is ≤10at.%, the atomic percentage of Si is ≥30at.%, the atomic percentage of O is ≤20at.%, and the atomic percentage of N is ≥40at.%; the thickness of the film layer on the side close to the etching stop film (20) is 5-45nm, and the thickness of the film layer on the side away from the etching stop film (20) is 30-70nm.

6. The mask blank according to claim 1, characterized in that The light shielding film (40) is a single-layer or multi-layer structure with a thickness of 30 to 65 nm.

7. The mask blank according to claim 6, characterized in that The light shielding film (40) is a single-layer structure, wherein the atomic percentage of Cr is ≥30 at.%, the sum of the atomic percentages of O and N is ≤55 at.%, and the atomic percentage of C is ≤15 at.%.

8. The mask blank according to claim 6, characterized in that The shading film (40) is a two-layer structure, and the relative refractive index of the film layer on the side away from the phase shift film (30) is greater than the relative refractive index of the film layer on the side close to the phase shift film (30); wherein the atomic percentage content of Cr in the film layer on the side close to the phase shift film (30) is ≤43at.%, the sum of the atomic percentage content of O and N is ≥37at.%, and the atomic percentage content of C is ≤20at.%, wherein the atomic percentage content of Cr in the layer on the side away from the phase shift film (30) is ≥35at.%, and the sum of the atomic percentage content of O and N is ≤65at.%; the thickness of the film layer on the side close to the phase shift film (30) is 35-55nm, and the thickness of the layer on the side away from the phase shift film (30) is 2-10nm.

9. The mask blank according to claim 8, characterized in that The light shielding film (40) further comprises a diffusion prevention layer, which is arranged on a side close to the phase shift film (30), wherein the atomic percentage content of Cr in the diffusion prevention layer is ≥35 at.%, and the sum of the atomic percentage content of O and N is ≤65 at.%; and the thickness of the diffusion prevention layer is 2-10 nm.

10. The mask blank according to claim 6, characterized in that The light shielding film (40) is a three-layer structure, comprising a first light shielding layer, a second light shielding layer and a third light shielding layer which are stacked in sequence, wherein the first light shielding layer is arranged on a side close to the phase shift film (30), and the third light shielding layer is arranged on a side away from the phase shift film (30), wherein the atomic percentage content of Cr in the first light shielding layer is ≤45at.%, the sum of the atomic percentage content of O and N is ≥35at.%, and the atomic percentage content of C is ≤20at.%, the atomic percentage content of Cr in the second light shielding layer is ≥45at.%, the atomic percentage content of non-metallic elements is ≤55at.%, the atomic percentage content of Cr in the third light shielding layer is ≤45at.%, the sum of the atomic percentage content of O and N is ≥35at.%, and the atomic percentage content of C is ≤20at.%; the thickness of the first light shielding layer is 10-35nm, the thickness of the second light shielding layer is 2-10nm, and the thickness of the third light shielding layer is 10-30nm.

11. The mask blank according to claim 6, characterized in that The light shielding film (40) is a four-layer structure, comprising a first light shielding layer, a second light shielding layer, a third light shielding layer and a fourth light shielding layer which are stacked in sequence, wherein the first light shielding layer is arranged on a side close to the phase shift film (30), and the fourth light shielding layer is arranged on a side away from the phase shift film (30), wherein the atomic percentage content of Cr in the first light shielding layer is ≤45 at.%, the sum of the atomic percentage content of O and N is ≥40 at.%, the atomic percentage content of C is ≤15 at.%, the atomic percentage content of Cr in the second light shielding layer is ≥35 at.%, and the third non-metallic element is ≥40 at.%. The atomic percentage of Cr in the third light-shielding layer is ≤65at.%, the atomic percentage of Cr in the third light-shielding layer is ≤45at.%, the sum of the atomic percentages of O and N is ≥40at.%, the atomic percentage of C is ≤15at.%, the atomic percentage of Cr in the fourth light-shielding layer is ≥35at.%, and the sum of the atomic percentages of O and N is ≤65at.%; the thickness of the first light-shielding layer is 15-30nm, the thickness of the second light-shielding layer is 2-10nm, the thickness of the third light-shielding layer is 15-30nm, and the thickness of the fourth light-shielding layer is 2-10nm.

12. The mask blank according to claim 1, characterized in that The hard mask (50) is a single-layer or multi-layer structure with a thickness of 2 to 15 nm. The atomic percentage of Si in each layer of the hard mask (50) is ≥30 at.%, and the sum of the atomic percentages of O and N is ≤70 at.%.

13. The mask blank according to claim 1, characterized in that The mask blank further comprises an anti-etching film (60), wherein the anti-etching film (60) is arranged on a surface of the hard mask (50) which is away from the light-transmitting substrate (10); the thickness of the anti-etching film (60) is 60-200 nm.

14. A method for manufacturing a mask blank, characterized in that: An etching stop film (20), a phase shift film (30), a light shielding film (40) and a hard mask (50) are sequentially deposited on a surface of one side of a light-transmitting substrate (10), wherein the etching stop film (20), the phase shift film (30), the light shielding film (40) and the hard mask (50) have the same definitions as those in claim 1.

15. The method for manufacturing a mask blank according to claim 14, characterized in that: The deposition is carried out by magnetron sputtering; during the deposition of the etching stop film (20), the phase shift film (30), the light shielding film (40) and the hard mask film (50), the working pressure is independently 0.1 to 0.4 Pa, the sputtering power is independently 200 to 3500 W, and the working gas is independently one or more of Ar, He, O2, N2, N2O, NO, NO2, CO2, CO, and CH4.

16. A method for manufacturing a phase shift mask, characterized in that: The phase shift mask is manufactured using the mask blank according to claim 1 as a raw material, and the manufacturing method comprises: Step S1, coating a first resist on the side of the hard mask (50) in the mask blank away from the light-transmitting substrate (10) to form a resist film (60), and sequentially performing exposure, baking and development to obtain a first stacked structure including a patterned first resist film (61); Step S2, using the patterned first resist film (61) in the first stacked structure as a mask, etching the hard mask film (50) in the first stacked structure, and obtaining a second stacked structure including the patterned hard mask film (51) after cleaning and removing the patterned first resist film (61); Step S3, using the patterned hard mask film (51) in the second stacked structure as a mask, etching the light shielding film (40) in the second stacked structure to obtain a third stacked structure including the patterned first light shielding film (41); Step S4, using the patterned first light shielding film (41) in the third stacked structure as a mask, etching the phase shift film (30) in the third stacked structure, wherein the patterned hard mask film (51) is removed during the etching process in step S4, thereby obtaining a fourth stacked structure including the patterned phase shift film (31); Step S5, coating a second resist on a surface of the fourth stacked structure that is away from the light-transmitting substrate (10), and sequentially performing exposure, baking and development to obtain a fifth stacked structure containing a patterned second resist film (62); Step S6, using the patterned second resist film (62) in the fifth stacked structure as a mask, etching the first shading film (41) in the fifth stacked structure, during the etching process of step S6, the etching stop film (20) is etched away, and after cleaning and removing the patterned second resist film (62), the phase-shift mask containing the patterned second shading film (42) is obtained.

17. The method for manufacturing a phase-shift mask according to claim 16, characterized in that: The hard mask (50) is a single-layer structure, or the hard mask (50) is a two-layer structure, the etching rate of the film layer on the side close to the light-shielding film (40) is lower than the etching rate of the film layer on the side away from the light-shielding film (40); or the hard mask (50) is a three-layer structure, the etching rate of the middle layer is lower than the etching rates of the other two adjacent layers.

18. A phase shift mask, characterized in that: The phase-shift mask is manufactured by the method for manufacturing a phase-shift mask according to claim 16 or 17.

Citation Information

Patent Citations

  • Mask blank, transfer mask, and semiconductor-device manufacturing method

    CN112740105A

  • Mask blank, phase shift mask, method for manufacturing phase shift mask, and method for manufacturing semiconductor device

    CN115769144A

  • Phase shift mask blank, process for preparation of phase shift mask blank, phase shift photomask and manufacturing method thereof

    TW200528915A

  • Photomask blank and photomask

    US20070212618A1

  • Phase-shift blankmask and photomask

    US20160054650A1